Electrocoagulation technque in enhancing COD and suspended solids removal to improve wastewater quality - Ni'am, M. F.; Othman, Fadil; Sohaili, J.; Fauzia, Z. (IWA Publishing, 2007)
This paper presents a preliminary study for the removal of COD and suspended solids in wastewater treatment by combining magnetic field and electrocoagulation (EC) technology. The experiments were carried out using batch apparatus and setup in the static method. Batch experiments with two monopolar iron (Fe) plate anodes and cathodes were employed as electrodes. Wastewater samples were prepared from milk powder with an initial COD of 1,140 mgL-1 and suspended solids of 1,400 mgL-1 and acidic conditions were employed (pH ~ 3). DC current was varied from 0.5–0.8 A and operating times were between 30 and 50 min. The results show that the effluent wastewater was very clear (turbidity ~9 NTU) and its quality exceeded the direct discharge standard. The suspended solids and COD removal efficiencies were as high as 30.6 and 75.5%, respectively. In addition, the experimental results also show that the electrocoagulation could neutralise the pH of wastewater.